5G: The Next Wave of Digital Society Challenges and Current Trends - Goudar, Swetha Indudhar; Hassan, Suhaidi; Habbal, Adib M. Monzer (Universiti Teknikal Malaysia Melaka, 2017)
The Internet that can easily connect global landscape is a fundamental component for business and communication.In the next decade, wireless network 5G will provide native support for a new kind of network infrastructure deployments, including the ultra-dense networks, multiple Radio Access Technology co-existence, direct Device to Device communication and many others.This article explores the new trends and challenges in the new digital wave.Further, it highlights the research areas in each feature and discusses the new approaches to handle huge populated devices demand.